Algérien en Nouvelle-Calédonie : Le destin calédonien du déporté Ahmed Ben Mezrag Ben Mokrani - Isabelle Merle (L’Année du Maghreb)
Ahmed Ben Mezrag Ben Mokrani, brother of the main leader of the Kabyl insurgency of 1871, and member of the prestigious Mokrani family, whose father had been Khalif of Medjana and an ally of the Bey of Constantine, was sentenced to death on March 27, 1873, for incitement to war and insurrectional facts. His sentence was commuted on October 13, 1873 to deportation to New Caledonia, where he landed in October 1874.If the man was famous for his role in the Unfaq Urrumi (the Kabyle uprising of 1871) much less is known of his life in New Caledonia where he resided until 1904. This paper deals with his long years in exile on this Pacific island, years in which Ahmed Ben Mezrag rallied French forces to fight the Kanak insurrection of 1878 and then moved to Nouméa to found and develop a postal company. The route is interesting because paradoxical. The proud Kabyle, a fighter against the French occupation, knew how to adapt to the «colonial situation» in New Caledonia by becoming a representative of the French cause and an honorable «inhabitant» of the colony. The challenge is to better understand the unfortunate or fortunate logics of such a denouement.